A Parkinson's disease risk analytics system based on handwritten Chinese characters - Chen, Jing (Nanyang Technological University, 2020)
Parkinson's disease (PD) is a debilitating neurodegenerative disorder. Early detection of the disease is important for effective treatment and can improve patients' quality of life. In order to achieve early detection, a population level screening tool is required. This paper introduces a prototype which aims to capture early signs of PD symptoms from users' Chinese handwriting on mobile screens. It can be seamlessly infused into everyday use.